INVESTIGATION OF TOXIC METALS POLLUTION IN WATER, SEDIMENT AND FISH AT ADEN COAST, GULF OF ADEN, YEMEN - Al-qadasy, Mohammed Kassem Othman; Babaqi, Abdulla Saleh; Al-Abyadh, Mukhtar Mohammed; Al-kaf, Ali Gamal Ahmed (Universal Journal of Pharmaceutical Research, 2017)
Objectives: This study investigates concentrations of toxic metals, Lead and Cadmium in water, sediments and fish organs (muscle, liver and gill). Collected from Aden coast, gulf of Aden in Yemen. Water samples and sediment were taken from nine locations. Methods: Four fish species were collected (Lethrinus mahsena; Epinephelus areolatus; Thunnus tonggol and Sphyraena jello) were collected from the local commercial fishermen of Aden city during winter 2011, Summer 2012 and winter 2013. Results: Lead concentration in sea water is 0.045-0.055 mg/l and Lead concentration in Sediment 33.512-35.726 µg/g dry wt., Cadmium concentration in sea water 0.006-0.010 mg/l, Cadmium concentration in sediment 1.944-2.004 µg/g dry wt., lead concentration is the highest in most fish gill samples 0.047-0.727 µg/g dry wt., where as in muscles is the lowest 0.020-0.116 µg/g dry wt., and in liver was 0.038- 0.267 µg/g dry wt. Cadmium concentration is the highest in most fish gill samples 0.033-0.609 µg/g dry wt., where as in muscles is the lowest 0.018- 0.073 µg/g dry wt., and in liver was 0.028-0.209 µg/g dry wt. Conclusion: By comparing the results obtained with other data obtained from the local and international studies, in addition to, comparing the results standard levels of these metals contaminated and adopted internationally and domestically and the pollution levels in Yemen is currently within the lower limits of pollution. Peer Review History: Received 4 October 2017; Revised 9 November; Accepted 29 December, Available online 15 January 2018 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Nicola Micale , University of Messina, Italy, nmicale@unime.it Dr. Omid Gholami , Sabzevar University of Medical Sciences, Iran, omidghphd@gmail.com